Effects of dexmedetomidine on renal tissue after lower limb ischemia reperfusion injury in streptozotocin induced diabetic rats. Issue 1 (1st January 2017) - Erbatur, Meral Erdal; Sezen, Şaban Cem; Bayraktar, Aslıhan Cavunt; Arslan, Mustafa; Kavutçu, Mustafa; Aydın, Muhammed Enes
ABSTRACT: Aim : The aim of this study was to investigate whether dexmedetomidine – administered before ischemia – has protective effects against lower extremity ischemia reperfusion injury that induced by clamping and subsequent declamping of infra-renal abdominal aorta in streptozotocin-induced diabetic rats. Material and Methods : After obtaining ethical committee approval, four study groups each containing six rats were created (Control (Group C), diabetes-control (Group DM-C), diabetes I/R (Group DM-I/R), and diabetes-I/R-dexmedetomidine (Group DM-I/R-D). In diabetes groups, single-dose (55 mg/kg) streptozotocin was administered intraperitoneally. Rats with a blood glucose level above 250 mg/dl at the 72nd hour were accepted as diabetic. At the end of four weeks, laparotomy was performed in all rats. Nothing else was done in Group C and DM-C. In Group DM-I/R, ischemia reperfusion was produced via two-hour periods of clamping and subsequent declamping of infra-renal abdominal aorta. In Group DM-I/R-D, 100 μg/kg dexmedetomidine was administered intraperitoneally 30 minutes before ischemia period. At the end of reperfusion, period biochemical and histopathological evaluation of renal tissue specimen were performed. Results : Thiobarbituric acid reactive substance (TBARS), Superoxide dismutase (SOD), Nitric oxide synthase (NOS), Catalase (CAT) and Glutathion S transferase (GST) levels were found significantly higher in Group DM-I/R when compared with Group C and Group DM-C. In the dexmedetomidine-treated group, TBARS, NOS, CAT, and GST levels were significantly lower than those measured in the Group D-I/R. In histopathological evaluation, glomerular vacuolization (GV), tubular dilatation (TD), vascular vacuolization and hypertrophy (VVH), tubular cell degeneration and necrosis (TCDN), tubular hyaline cylinder (THC), leucocyte infiltration (LI), and tubular cell spillage (TCS) in Group DM-I/R were significantly increased when compared with the control group. Also, GV, VVH, and THC levels in the dexmedetomidine-treated group (Group DM-I/R-D) were found significantly decreased when compared with the Group DM-I/R. Conclusion : We found that dexmedetomidine − 100 μg/kg intraperitoneally – administered 30 minutes before ischemia in diabetic rats ameliorates lipid peroxidation, oxidative stress, and I-R-related renal injury. We suggest that dexmedetomidine administration in diabetic rats before I/R has renoprotective effects.